THE EFFECT OF THE STORY “MY BODY IS MINE” USING AGAIN (AGAM INONG) DOLL MEDIA ON SEXUAL EDUCATION AMONG CHILDREN AGED 6–7 YEARS - Risna Risna; Novita Sari; Mutia Rezky (Universitas Bina Bangsa Getsempena, 2026)
Storytelling method using puppets is the right and strategic choice to support the learning process of early childhood. Therefore, the application of this method is very feasible and can be integrated into the sexual education program and learning of various children's educational institutions. The purpose was to determine the effect of the story of my body is mine using the media of the doll again (agam inong) on ​​the sexual education of children aged 6-7 years at SDN 1 Teubeng, Pidie District, Pidie Regency. The research method used was an experimental essay with a one group pretest posttest design. The study was conducted on May 21-24, 2025. The population were all children aged 6-7 years as many as 105 people with an accidental sampling technique of 51 people. The results of the study showed that there was an effect of the story of my body is mine using the media of the doll again (agam inong) on ​​the sexual education of children aged 6-7 years, difference of 0.353 and this difference shows a significant difference as seen from t count = 5.222 and t-table = 2.009 with a P-value of 0.000. So it can be concluded that there is an influence of the story of my body belongs to me using the media of the doll again (agam inong) on ​​the sexual education of children aged 6-7 years. It is recommended that teachers pay attention to the needs of students'/children's stories to increase insight and instill character values.